Analysis of the Linguistic Aggregation Operator LAMA in Group Decision Making Process - Peláez, J. I. (2003)
At the present time different processes exist in group decision making processes which have been developed using different operators of linguistic aggregation. These operators satisfy a number of axioms that guarantee correct aggregation from a social point of view. The present work analyses, the operator of majority additive aggregation LAMA. Further, It is shown the rationality of its aggregation way; finally it present the properties of the LAMA operator, and how its operator is appropriate to solve group decision making problems from individual linguistic preference relations.